ANALYSIS OF SCIENTIFIC RESEARCH ON TAX POLICY STRATEGY (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article deals with ensuring the effectiveness of the fiscal system in the new development strategy of our republic. Tax policy plays a very important role in the economic policy of any country. Tax policy is closely connected with other types of economic policy of the state and influences them. The correct development of tax policy and the definition of its strategic and tactical directions is a very relevant and complex process. This article analyzes the content of the tax policy, its strategy and tactics, as well as the priority areas of the tax policy of Uzbekistan today.